Clinical Education for the Health Professions 2021
DOI: 10.1007/978-981-13-6106-7_138-1
|View full text |Cite
|
Sign up to set email alerts
|

Practice Education in Lockdown: Lessons Learned During the COVID-19 Global Pandemic

Abstract: The COVID-19 global pandemic has had large impacts on practice education opportunities for students enrolled in health professional courses. In response, educators and clinical supervisors have been required to change the ways in which pre-clinical and clinical education opportunities are delivered. This chapter presents several methods (tele-placement, tele-supervision, online simulated placements, and online facilitated reflective learning) which were adopted for occupational therapy students in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As lockdown strategies were put in place to respond to COVID‐19, health professionals, including occupational therapists, had to rapidly adapt service delivery to telehealth and digital platforms (Robinson et al, 2021 ). While perceived as limiting some opportunities, practice educators in our study used digital and telehealth platforms to their advantage by using technology creatively, including giving students feedback in almost ‘real‐time.’ Our findings align with Twogood et al ( 2020 ) who reported on a physiotherapy student virtual clinic model developed in response to COVID‐19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As lockdown strategies were put in place to respond to COVID‐19, health professionals, including occupational therapists, had to rapidly adapt service delivery to telehealth and digital platforms (Robinson et al, 2021 ). While perceived as limiting some opportunities, practice educators in our study used digital and telehealth platforms to their advantage by using technology creatively, including giving students feedback in almost ‘real‐time.’ Our findings align with Twogood et al ( 2020 ) who reported on a physiotherapy student virtual clinic model developed in response to COVID‐19 restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Twogood et al ( 2020 ) found that in the absence of students practising their hands‐on skills and educators attempting to create an artificial environment for this, educators focused on the development of skills not previously included in practice education such as the delivery of virtual rehabilitation (also referred to telerehabilitation or teletherapy). This has not been reported specifically for occupational therapy practice education contexts, nor across a broad range of settings, yet some promising digital approaches are emerging (Robinson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation